Effect of Micro Lime on The Ambient Cured Sugarcane Bagasse Ash-Based Geopolymer Concrete - Kamau, Keithy; Omondi, Benard; Oyaro, Janet (Jurnal Teknik Sipil, 2023)
Geopolymer concrete has been the ideal replacement for Ordinary Portland cement concrete in producing green concrete. The binder in geopolymer concrete is a cementitious paste made from amorphous Aluminosilicate and activated by an Alkaline solution. The geopolymerization process is initiated at elevated temperatures. Thus, the curing requires elevated temperatures. This curing method limits the application of geopolymer concrete in the construction industry. In a geopolymer mix, the presence of Calcium ions allows the formation of Calcium Aluminate Silicate and Calcium Silicate Hydrate gels, allowing ambient temperature curing. Therefore, this study investigates the effect of micro lime on the Sugarcane Bagasse Ash-based geopolymer concrete. The micro lime was added to the geopolymer concrete in 1, 3, 5 and 7% by the Sugarcane Bagasse Ash weight. A mix design was based on a Densified Mix Design Algorithm. The tests carried out included compressive strength and water absorption. Ambient curing of the SCBA-based geopolymer concrete was achieved with 1% of the micro lime. The compressive strength increased with the increase of the micro lime, 10N/mm2 at 1%, to 18.25N/mm2 at 7% micro lime. The ambient temperature-cured geopolymer concrete at 3% micro lime had the lowest water absorption rate.